Effect of varying diameter on the performance ofindustrial scale gas cyclone dust separators. (2015) - Brar, L.S.; Sharma, R.P.
Abstract: The present work deals with the study of varying diameters on the performance of the gas cyclones. Three different diameters viz. 0.8D, 1.0D, and 1.2D have been considered (D being the standard diameter of cyclone and the constants are the scaling factors) and their effects on the pressure drop, collection efficiency, and cut-off diameter have been evaluated. Navier-Stokes equations are discretized using finite volume methods which are solved iteratively with commercially available CFD code FLUENT 6.3.2 on block unstructured hexahedral mesh. Reynolds stress model (RSM) has been used as a closure model for Reynolds averaged Navier-Stokes equations, which solves for stress tensors together with the equation for the dissipation rates. It has been found that increase in cyclone diameter increases the collection efficiency at the expense of increasing pressure drops across the gas cyclones.